Travessias... movimentos migratórios em comunidades rurais no sertão do norte de Minas Gerais - Paula, Andréa Maria Narciso Rocha de (2009)
The objective of this work is to study and to understand - through their traditions and changes in their ways of life and work - the construction of the agricultural identity and the peasant reproduction strategies in the migratory process of the migrant people who returned to their place of origin in the North of Minas Gerais. For this purpose we concentrate our work in a small and traditional "ribeirinha" community and also with the subjects/actors/personages of João Guimarães Rosa's romance, stories and novels.We start from the assumption that the migratory process modifies and alters the ways of life and work of the rural men and women, but that at the same time they possess a structural and symbolic condition of territorial identity, otherness and recognition of being part of the peasant agricultural world.We affirm the space as the promoter of the transformations in the environment and the way of life upon which people, families and communities interact with the scenes, spaces, places and territories of their living, leaving and - one day - coming back. We also understand Man as the producer of these transformations in and through culture. Supported by the phenomenological contributions and references brought by Anthropology, Literature and Sociology, we intend to value the dimensions of cultural order also in the scope of Geography Sciences under the optics of the place, by doing an analytical interpretation of the categories of time-space; territory-territoriality; space-place; and perception.